The use of the Gait Deviation Index for the evaluation Post-stroke Hemiparetic Subjects - Alcantara,Carolina C. (2017)
BACKGROUND: The Gait Deviation Index, initially conceived to evaluate the gait of children with cerebral palsy, has been used as a quantitative parameter of gait pattern changes of individuals with other conditions. However, there are no studies evaluating changes in the gait pattern of chronic hemiparetic post-stroke subjects based on this index. AIMS: To characterize the changes in gait pattern according to the Gait Deviation Index and gait spatiotemporal parameters of chronic hemiparetic subjects compared to healthy subjects. METHODS: Retrospective study. Data were obtained from the database of the Gait Laboratory of Hospital Israelita Albert Einstein. Thirty subjects were included in this study, with previous unilateral, ischemic or hemorrhagic chronic stroke (time post-lesion > 6 months) and ability of walking classified as 2, 3, 4 or 5 according to Functional Ambulation Category. Data from 87 healthy subjects were included in control group, obtained from a normality database. Statistical analysis was applied through the Kruskall Wallis test, followed by Mann-Whitney post-hoc test, considering a critical p value <0.05. RESULTS: The Gait Deviation Index scores were decreased for both paretic (64.69 ± 16.29) and non-paretic limbs (64.88 ± 15.00) compared to control (101.01 ± 10.12; p < 0.001). No differences were observed in Gait Deviation Index scores between paretic and non-paretic limbs (p > 0.99). CONCLUSION: The findings of the current study demonstrate that the Gait Deviation Index may be a sensitive parameter to identify changes in the gait pattern of chronic hemiparetic post-stroke subjects.